Eco-friendly steelmaking: Exploring the potential of plant-based binder Acacia gum for iron ore pelletizing - Hassan Koohestani; Jalal Hasanpoor; Behrooz Ghasemi (Case Studies in Chemical and Environmental Engineering)
In the pelletizing process, a crucial stage in the iron and steel production industry, binders play a significant role. Bentonite, the conventional binder in iron pellet production, contains impurities that can be transferred to the final product, reducing its quality. In recent years, researchers have been seeking suitable substitutes for bentonite. In this research, the effect of Acacia gum (gum arabic) as an organic binder in the pelletizing process has been investigated, and the results have been compared with pellets produced using bentonite. Accordingly, different magnetite pellets were made under various binders and thermal conditions. The X-ray diffraction (XRD) results showed that magnetite was converted to hematite during the calcination process at 1100 °C. In the XRD pattern of samples containing Acacia gum, hematite phase peaks were observed, and no significant impurities were identified. Based on the thermogravimetric analysis (TGA) results, the organic binder was completely decomposed at 300 °C, and at 900 °C, the binder was completely removed from the pellet. In this case, the pellets' strength was due to the particles' sintering. Investigation of the mechanical properties of the pellets showed that pellets containing 2 % bentonite +3 % Acacia gum with compressive strength and dropping number 1.380 kN/pellet and 4.1, respectively, could provide the necessary properties.